ChemInform Abstract: Enhancing the Thermoelectric Properties of Germanium Antimony Tellurides by Substitution with Selenium in Compounds GenSb2(Te1‐xSex)n+3 (0 ≤ x ≤ 0.5; n ≥ 7). Issue 28 (15th July 2014) - Rosenthal, Tobias; Urban, Philipp; Nimmrich, Kathleen; Schenk, Ludwig; de Boor, Johannes; Stiewe, Christian; Oeckler, Oliver
Abstract Bulk samples of GenSb2(Te1‐xSex)n+3 (0 < x ≤ 0.5; 7 ≤ n ≤ 19) are prepared by melting stoichiometric amounts of the elements (silica glass ampoules, 950 °C, 2 h, quenching) followed by annealing at 580 °C for 2 days (630 °C in case of Ge19Sb2 (Te0.8Se0.2)22) and quenching.